Food and feeding habits of Indian sciaenids - A review - Bhakta, Dibakar; Kumar Das, Sudhir; Das, Basanta Kumar (Indian Journal of Fisheries, 2023)
An attempt was made in the present article to review the food and feeding habits of the fishes of the family Sciaenidae from Indian waters. Members of the Sciaenidae family are commonly referred to as croakers or drums because of the sound produced by their swim bladders. Sciaenids are distributed in tropical and sub-tropical oceans. They are carnivorous, feeding mainly on crustaceans, small fish, molluscs, annelids and polychaetes and exhibit cannibalism. Sciaenids display differences in food preferences between early stages and adults; the former prefers zooplankton and crustaceans, and the latter mainly smaller teleosts. The feeding intensity was found to be higher in smaller groups compared to mature fish. Considerable temporal variations were recorded in food item occurrence, indicating an empty stomach during peak breeding and a wide spectrum of food items during other seasons. Keywords: Croakers, Feeding intensity, Food and feeding habits, Sciaenids